2017
DOI: 10.2147/bctt.s139963
|View full text |Cite
|
Sign up to set email alerts
|

The ABC7 regimen: a new approach to metastatic breast cancer using seven common drugs to inhibit epithelial-to-mesenchymal transition and augment capecitabine efficacy

Abstract: Breast cancer metastatic to bone has a poor prognosis despite recent advances in our understanding of the biology of both bone and breast cancer. This article presents a new approach, the ABC7 regimen (Adjuvant for Breast Cancer treatment using seven repurposed drugs), to metastatic breast cancer. ABC7 aims to defeat aspects of epithelial-to-mesenchymal transition (EMT) that lead to dissemination of breast cancer to bone. As add-on to current standard treatment with capecitabine, ABC7 uses ancillary attributes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 244 publications
(299 reference statements)
0
9
0
Order By: Relevance
“…Among them, HSD11B1-AS1 (lnc-LAMB3-1), AC008695.1, and MAGEC2 have been reported to be key for tumor cell EMT. 3335 We found that the extent of EMT was significantly reduced after treatment with a TGF-β1 inhibitor, as shown by significant changes in the expression of EMT marker proteins. Taken together, these findings revealed that expression changes of lncRNAs are closely related to the occurrence and development of EMT in CNE1 cells.…”
Section: Discussionmentioning
confidence: 83%
“…Among them, HSD11B1-AS1 (lnc-LAMB3-1), AC008695.1, and MAGEC2 have been reported to be key for tumor cell EMT. 3335 We found that the extent of EMT was significantly reduced after treatment with a TGF-β1 inhibitor, as shown by significant changes in the expression of EMT marker proteins. Taken together, these findings revealed that expression changes of lncRNAs are closely related to the occurrence and development of EMT in CNE1 cells.…”
Section: Discussionmentioning
confidence: 83%
“…Although the mechanism underlying the anti-viral and anti-tumor effects of ribavirin has not yet been fully elucidated, several participating/possible processes have been mentioned above. Kast et al (28) pointed out the following major mechanisms of action, particularly related to the anti-viral action: i) actual intermingling within the viral RNA; ribavirin enters the cell via a nucleoside transport mechanism, subsequently inhibiting/altering viral RNA synthesis, ii) structural analogy to GTP; incorporation into the cell passively, then binding/inhibiting RNA polymerase/RNA synthesis, iii) immune clearance; immune-stimulation by up-regulation of cytokines to shift the Th1/2 cell balance to Th1 dominance, iv) inhibition of eIF4E; thereby inhibiting mRNA capping and translation initiation, v) modulation of IFN-related gene expression, vi) inhibition of IMPDH; with consequent depletion of intracellular GTP, and vii) RNA mutagen; following triphosphorylation, ribavirin triphosphate is incorporated into replicating RNA viral RNA polymerases with consequent induction of viral mutagenesis. These processes are attractive as factors in the repurposing of the anti-viral ribavirin as an anti-tumor agent, and also in the mechanism underlying the synergistic effect of ribavirin in combination with other agents.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, this same study found that in addition to inhibition of eIF4E, there was significant reduction in the activity of matrix metalloproteinase-3 (MMP-3) and matrix metalloproteinase-9 (MMP-9). These proteins are integral to mesenchymal cancer cell invasion and epithelial-tomesenchymal transition (EMT) for metastasis, and these findings have led to proposed treatment schemas for using ribavirin in combination with other agents that target distinct pathways involved in EMT (23,24). This has resulted in phase I/II clinical trials assessing the efficacy of ribavirin in metastatic breast cancer and other solid tumors, the results of which have yet to be reported (NCT01056757 and NCT01309490).…”
Section: Metastatic Breast Cancermentioning
confidence: 99%